Investigation of the allergens in 2,316 children with allergic rhinitis from Guangdong, China - Zhang, Nannan; Wu, Yunwen; Wei, Zequn; Li, Jinen; Shi, Jiao; Cai, Rong; Huang, Hailing; Ouyang, Siyuan; Zhang, Qingfeng (Frontiers in Pediatrics, 2022)
Allergic rhinitis (AR) is one of the popular childhood diseases, bringing physical and metal burdens to the children and their families. The study was performed to detect common allergens eliciting AR in children, to investigate the prevalence of allergens in different age and gender cohorts, and to provide a reliable basis for clinical prevention and treatment of AR during childhood. We measured serum-specific IgE and performed inhalant and ingestion allergen examinations in 2,316 children with AR, in collaboration with BioSciTec GmbH. The prevalence of different allergens was determined according to gender, age, severity, and season. Among the 2,316 AR cases, the top five inhalant allergens were Dermatophagoides pteronyssinus (1,674 cases, 72.3%), Dermatophagoides farinae (1,520 cases, 65.6%), Blomia tropicalis (1,477 cases, 63.8%), Cockroach (602 cases, 26.0%), and Dog hair (602 cases, 26.0%). The top five ingestive allergens were Milk (1,111 cases, 48.0%), Egg white (543 cases, 23.4%), Shrimp/Crab (425 cases, 18.4%), Beef/Mutton (422 cases, 18.2%), and Egg yold (329 cases, 14.2%). AR severity analyses showed that 50.9% (1,180 cases) of D. pteronyssinus allergies were above level three, 47.9% (1,109 cases) of D. farinae allergies were above level three, only 23.3% (539 cases) of B. tropicalis allergies were level three, and B. tropicalis allergies were mainly of level 2. Other AR-inducing allergens mainly produced level one or two reactions. Regarding ingestion allergens, 7.9% (183 cases) of milk allergies and 4.7% (108 cases) of Shrimp/Crab allergies were above level three, and other allergens induced AR mainly of level one or two. The study investigated the major allergens eliciting AR in children from Guangdong, China, assessed the prevalence and severity among cohorts regarding age, gender, and season, and produced essential information on childhood AR, laying important references for AR prevention and treatment in the future.